Penanaman Karakter Religius Melalui Kegiatan Pembiasaan Pagi Serta Relevansinya Dengan Nilai P2RA - Mubarokah, Gina; Holis, Ade; Amirudin, Ja'far; Anisah, Ani Siti (Didaktika, 2025)
Religious character education is becoming increasingly urgent in correcting moral deterioration due to the impact of globalization. Based on previous research, there are a lot of studies that focus on the development of religious character through morning habituation activities, but research that links morning habituation activities with the value of Rahmatan lil-Alaimin student profiles has not been widely discussed. Considering that the curriculum from time to time is developing, therefore this research is important because it is a novelty in developing research topics. The purpose of this study is to describe the process of implementing morning habituation activities in instilling religious character and the extent to which this activity can improve the religious character of MIN 2 Garut students which is in line with the values of the Rahmatan lil-Alamin student profile. The method used in this study uses a qualitative descriptive approach of the case study method. The data collection process is carried out by observation, documentation, interviews, and data analysis techniques using interactive analysis with data reduction, data analysis, and conclusions drawn. Based on the findings of the research, by carrying out morning habituation activities consistently, students began to show progress in various aspects, both moral and intellectual, including awareness to be enthusiastic about participating in habituation activities and discipline in carrying out worship. The results of this research can be used as a basis for developing a more effective curriculum and learning programs for instilling religious character through morning habituation activities.